(untitled) (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2012)
In work widely known methods of range measuring are short characterized. The basic attention is given features of signal processing in a correlation method of range measuring. The signal with angular modulation with one-voice-frequency fluctuation is used as a probing signal. The absence of Doppler effect on the formation of the correlation integral, the frequency instability of the transmitter, the phase change on reflection from the target is presented. It is noticed that the result of signal processing in the range measuring instrument is reduced to formation on an exit one-voice-frequency harmonious fluctuation equal to modulating frequency that provides high characteristics of a radio range finder.